2019
DOI: 10.1111/imb.12625
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of heat shock protein 90 suppresses Bombyx mori nucleopolyhedrovirus replication in B. mori

Abstract: Heat shock protein 90 (Hsp90) plays a very important role in facilitating the replication of many viruses. Until now, little has been known about the role of Hsp90 in Bombyx mori virus infection. In this study, we explored the role of BmHsp90 in B. mori nucleopolyhedrovirus (BmNPV) replication. We found that BmHsp90 inhibition by geldanamycin (GA) significantly reduced the BmNPV titre, the protein expression level of BmNPV nucleocapsid protein 39 (VP39) and the transcript level of BmNPV genes. Silencing the hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…It is not surprising to observe inhibition of SARS-CoV-2 by geldanamycin, given that a large number of viruses have been reported subject to geldanamycin inhibition. These include encephalomyocarditis virus (EMCV) (59), bombyx mori nucleopolyhedrovirus (6062), pseudorabies virus (63), H5N1 influenza A virus (64), porcine circovirus 2 (65), chikungunya virus (66, 67), porcine reproductive and respiratory syndrome virus (68), enterovirus 71 (69, 70), herpes simplex virus type 2 (71), human cytomegalovirus (71, 72), Theiler’s murine encephalomyelitis virus (73), Ebola virus (74), hepatitis E virus (75), influenza virus (76), hepadnavirus (77), hepatitis B virus (77), flock house virus (78), vesicular stomatitis virus (79), hepatitis C virus (80, 81), herpes simplex virus type 1 (82, 83), vaccinia virus (84), RT and Rauscher leukemia virus (85). This broad antiviral activity of geldanamycin is primarily attributed to its antagonism of HSP90.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising to observe inhibition of SARS-CoV-2 by geldanamycin, given that a large number of viruses have been reported subject to geldanamycin inhibition. These include encephalomyocarditis virus (EMCV) (59), bombyx mori nucleopolyhedrovirus (6062), pseudorabies virus (63), H5N1 influenza A virus (64), porcine circovirus 2 (65), chikungunya virus (66, 67), porcine reproductive and respiratory syndrome virus (68), enterovirus 71 (69, 70), herpes simplex virus type 2 (71), human cytomegalovirus (71, 72), Theiler’s murine encephalomyelitis virus (73), Ebola virus (74), hepatitis E virus (75), influenza virus (76), hepadnavirus (77), hepatitis B virus (77), flock house virus (78), vesicular stomatitis virus (79), hepatitis C virus (80, 81), herpes simplex virus type 1 (82, 83), vaccinia virus (84), RT and Rauscher leukemia virus (85). This broad antiviral activity of geldanamycin is primarily attributed to its antagonism of HSP90.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanism of BmNPV‐host interaction is still poorly understood. Shang et al (2020) found that BmHSP90 inhibition by GA significantly reduced the BmNPV titer, the protein expression level of BmNPV nucleocapsid protein 39 (VP39), and the transcript level of BmNPV genes. Silencing the hsp90 gene in BmN cells suppressed BmNPV replication whereas overexpression of hsp90 promoted the replication of BmNPV, however, the mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that HSP90 is essential for the replication of various viruses. Our previous study indicated that inhibition of HSP90 by GA can suppress BmNPV proliferation in B. mori (Shang et al, 2020), but the mechanism is uncovered. In this study, we aim to explore the underlying molecular mechanism of HSP90 inhibitor in suppression of BmNPV proliferation from the aspect of miRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of BmSTAT in BmN cells increased the number of cells in the G2 phase of the cell cycle (54) and host resistance to BmNPV, but not to BmCPV (55). Additionally, inhibition of Hsp90 can cause upregulation of BmSTAT expression and suppression of BmNPV replication in the BmN cell (56), but it is not clear how Hsp90 can be linked to JAK/STAT. The extracellular ligand and effector molecules of this pathway in response to viral infection in silkworms have not been clearly identified and merit further investigation.…”
Section: Jak/stat Pathwaymentioning
confidence: 99%